A study of flexural strength of rectangular beam using polystyrene beads as a partial replacement of fine aggregates - Nazathul Najwa, Sulaiman (2016)
Lightweight concrete (LCW) has been successfully used and it is very well known due to its lower density than normal concrete. It is created using materials that has a low density. Nowadays, most studies on LWC more towards about the influence of materials on the strength. Many researchers prove that polystyrene beads one of the best things in lightweight category to combine with concrete. The element that made up from polystyrene beads can involve in structural or non-structural parts. The aim of this study is to produce a lightweight concrete beam that is produced from expanded polystyrene beads as a partially replacement to fine aggregate. In this study, the strength of LCW with different density such as 2077 kg/m3 for normal concrete, 1344 kg/m3 for ratio 1, 1664 kg/m3 for ratio 2 and 1614 kg/m3 for ratio 3 was produces with different percentage of polystyrene beads as partially replacement of fine aggregates. Four series of LWC mix design including normal concrete with ratio of 3:1:0, ratio 1; 1:2:1, ratio 2; 1:2.5:0.5 and ratio 3; 1:1.5:1.5 which is comprises of 0%, 12%, 25% and 37.5% as partially replacement of fine aggregates (by total weight of fine aggregates) were considered and river sand was used as fines aggregates. There are two types of test were conducted namely compressive strength and flexural strength. The tests were conducted in order to determine the effect of percentage of polystyrene beads due to different curing ages. The results showed that, the increasing the percentage of polystyrene beads as river sand replacement, the strength decreasing significantly due to compressive strength and flexural strength for all mixes. It is also showed that the curing ages crucially affect its strength. Overall, it is indicated that the optimum mix design to produce LWC-Polystyrene Beads was obtained by using 12% of polystyrenes beads as partially replacement of fine aggregate.